Urgensi fotosintesis bagi makhluk hidup berdasarkan ‎perspektif al-Qur’an - Zahra, Elok Dzikrinina Amelya (Maliki Interdisciplinary Journal, 2023)
Plants are one of the living things found in the universe. Plants have a very important role for life. The characteristic feature of plants that are not shared by other organisms is the ability to make their own food. Photosynthesis is a biochemical process for the formation of food substances such as carbohydrates carried out by plants, especially plants that contain green leaf substances or chlorophyll. The process of photosynthesis is supported by the presence of chlorophyll, water, sunlight and carbon dioxide (CO2). It is this chlorophyll in plants that drives the synthesis of food molecules in chloroplasts. Water and sunlight are also other important ingredients in supporting the smooth process of photosynthesis. Sunlight is the main source of energy for photosynthesis reactions. Sunlight is needed by plants as an energy source to carry out 2 stages of reactions in photosynthesis, namely the light reaction or light dependent reaction (LDR) that occurs in the thylakoids and the Calvin cycle or light independent reaction (LIR) that occurs in the stroma. Photosynthesis has an important role for the life of living things, including producing energy, producing oxygen and producing fruit and glucose.